Immobilization of lectin preparations from Moringa oleifera seeds in inert supports for water purification - Santos, Andréa F. S. (2008)
Humic acids are linked to the formation of carcinogenic disinfection by-products upon chlorination of drinking water. In this work the first focus was tocharacterize the affinity of protein preparations obtained from Moringa oleifera seeds (extract, E, fraction, 0-60F and M.oleifera lectin, MoL) to bind humic acids. The second focus was to select a suitable support to immobilize MoL and to assess humic acid removal from water in a packed bed column. Specific hemagglutinating activity (SHA) decreased by 94 % for both E and MoL and by 50 % for 0-60F in the presence of a commercial humic acid. Humic acid-MoL precipitation bands were observed in the diffusion gel. Both results indicate humic acid-lectin binding. Carbohydrates, potassium and calcium ions as well as pH va-lues affected the SHA of MoL. Ahumic acid removal of 30.4 mg/g (expressed as mass of humic acid per mass of support) was obtained in a column packed with sepharose immobilized MoL receiving a 20 mg/L of carbon humic acid solution.